Is lymph node dissection necessary for resectable intrahepatic cholangiocarcinoma? A systematic review and meta-analysis. Issue 7 (July 2019) - Zhou, Rui; Lu, Dihan; Li, Wenda; Tan, Wenliang; Zhu, Sicong; Chen, Xianqing; Min, Jun; Shang, Changzhen; Chen, Yajin
Abstract: Background: The objective of this meta-analysis was to evaluate the effectiveness and safety of lymph node dissection (LND) in patients with intrahepatic cholangiocarcinoma (ICC). Methods: A literature search with a date range of January 2000 to January 2018 was performed to identify studies comparing lymph node dissection (LND+) with non-lymph node dissection (LND-) for patients with ICC. The LND + group was further divided into positive (LND + N+) and negative (LND + N-) lymph node status groups based on pathological analysis. Results: 13 studies including 1377 patients were eligible. There were no significant differences in overall survival (OS) (HR 1.13, 95% CI 0.94–1.36; P = 0.20), disease-free survival (DFS) (HR 1.23, 95% CI 0.94–1.60; P = 0.13), or recurrence (OR 1.39, 95% CI 0.90–2.15; P = 0.14) between LND + group and LND-group. Postoperative morbidity was significantly higher in the LND + group (OR 2.67, 95% CI 1.74–4.10; P < 0.001). A subset analysis showed that OS was similar between LND + N- and LND-groups (HR 1.13, 95% CI 0.82–1.56; P = 0.450). However when comparing, OS of the LND-group to the LND+N+ group there was a significant increase in OS for the LND-group (HR 3.26, 95% CI 1.85–5.76; P < 0.001). Conclusions: LND does not seem to positively affect overall survival and is associated with increased post-operative morbidity.